56 SARCOPENIA SCREENING FOR INDEPENDENTLY MOBILE STROKE PATIENTS IN AN ACUTE HOSPITAL SETTING. (25th October 2022) - Murphy, D; Crowley, A; Fitzpatrick, M
Abstract: Background: Sarcopenia appears to be under-assessed and under-treated in the stroke population. It has been suggested by EWGSOP2 criteria, that if there is a clinical suspicion of sarcopenia, an intervention for this is appropriate. In order to establish the need for this in the independent stroke population an audit of the clinical prevalence of sarcopenia in independently mobile stroke patients was completed. Methods: An excel spreadsheet was compiled of a convenient sample of stroke patients who were independently mobile post stroke. Their grip strength and five times sit to stand was audited along with the patient's age and sex. This information was then used to assess for sarcopenia risk as per the EWGSOP2 guidelines. Results: Fifteen patients were assessed, all of whom were independently mobile with or without an aid post admission for a primary diagnosis of acute stroke. Their age ranged from 64 to 86. Of these patients 93% were deemed likely to have sarcopenia based on their clinical assessment. This was based on grip strength measurements and time taken to complete five sit to stands. These clinical signs indicate low muscle strength and likely sarcopenia. Conclusion: Currently no intervention is provided for these patients in relation to sarcopenia from the physiotherapy department. This audit indicates that this is currently an unmet need and these patients may benefit from an intervention to address this significant issue.